Usability Dimensions for Chronic Disease Mobile Applications: A Systematics Literature Review - Zahra, Fatima; Mohd, Haslina; Hussain, Azham; Omar, Mazni (2018)
Many mobile health (m-health) applications have been developed in recent years. However, only few statistical evidences on the acceptability and usability issues have been discussed by previous studies. In addition, the requirements for the chronic disease applications are often overlooked. Failure to include the requirements has led to the rejection of the m-health applications. The existing usability evaluation models consist only the general dimensions for evaluating mobile applications, which are unable to capture the complexities of different categories of mobile applications. Such categories require different functional and nonfunctional requirements; thus, customized usability evaluation models are required. The main objective of this paper is to provide usability dimensions and measurement to evaluate the chronic disease mhealth applications users’ requirements. The related data were gathered by interviewing selected users and analyzed using Nvivo. The Systematics Literature Review (SLR) approach was also used to select 60 articles from established journals in the Computer Science and Medical. From these articles, 15 relevant dimensions for chronic disease were determined which were later simplified into six dimensions. These six dimensions provide the basis for developing the development of the usability evaluation model for chronic disease mobile applications. This evaluation model can facilitate application developers in creating better applications that will increase the adoption of the chronic disease mobile applications in the clinical practice. Ultimately, the overall impact of these applications may increase.